Maldives : 2014 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for the Maldives. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Maldives' real economy has picked up. Growth is estimated to have reached 5 percent in 2014 with stronger tourism activity driven by a rapid expansion from Asian markets and a tepid recovery from Europe. The IMF staff expects growth to be about 5 percent in 2015. Weaker import prices have pushed down inflation to low levels. Growth is expected to remain relatively strong in the near term, though the fiscal adjustment envisaged in the 2015 Budget will have a mildly negative effect on growth.